(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
This study employs a descriptive research design to examine socio-economic and demographic factors influencing safe delivery practices. Both primary and secondary data were utilized. Primary data were collected from 120 women aged 15–49 years across three wards of Kohalpur Municipality, Banke District, Nepal, using structured interviews. Respondents were selected through random sampling, focusing on women with at least one child under five years. Secondary data were obtained from municipal profiles and health posts. Data collection tools were validated by experts and finalized under the guidance of an advisor. Simple statistical tools were used for analysis, with findings presented in tables, graphs, and percentages. The study underscores the impact of education, awareness, and accessibility to healthcare facilities in improving maternal health outcomes and promoting safe delivery practices.